Fungal diseases of three aromatic rice (Oryza sativa L.) (Journal of Bangladesh Academy of Sciences, 2011)
Seeds of three aromatic rice (Oryza sativa L.) var. Kalijira, Kataribhog and BR 34 Jira dhan were tested by Blotter method for identifying their seed borne fungi. Fungi associated with seeds were Aspergillus niger, Apergillus sp., Carvularia sp., Cladosporium sp., Colletotrichum sp., Fusarium sp., Pyrenochaeta oryzae and Sarocladium oryzae. Infected samples were collected from the field starting from maximum tillering stage to grain filling stage of plant growth. After maximum tillering stage three fungal diseases were recorded on the stems and sheaths. Sheath rot was recorded on all the three rice varieties, stem rot was recorded on Kalijira and sheath blotch was recorded on Kataribhog. The pathogens of sheath rot, Sarocladium oryzae, sheath blotch, Pyrenochaeta oryzae and stem rot, Sclerotium oryzae were frequently associated with the respective samples. This is the first report of disease on aromatic rice plant for Bangladesh. Key words: Fungal diseases; Aromatic rice DOI: 10.3329/jbas.v34i2.6860Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 163-170, 2010